Mr. Bennett e Mrs. Brown (1924) de Virginia Woolf - Tradução - Carla Morais Pires (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
Carla Morais Pires’s new translation of Mr. Bennett e Mrs. Brown (1924) by Virginia Woolf into Portuguese.